PENDIDIKAN KARAKTER MENGGUNAKAN METODE BERCERITA 5-6 TAHUN PAUD TAMAN PENA KABUPATEN KUBU RAYA - Rodiana, Lina; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Character education is the cultivation of character values which include various components such as knowledge, awareness or will, and actions to implement these values, both towards God Almighty, oneself, others, the environment and nationality. Storytelling is a method that can be used as a tool or bridge to achieve the vision and mission of character education because storytelling can be an effective method of conveying character values to children. This study aims to describe the implementation of character education using the storytelling method for children aged 5-6 years at PAUD Taman Pena, Kubu Raya Regency. In particular, this study aims to describe character education for hard work, independence and creativity. The methode used in this study is a descreiptive research method with a qualit approach. the data source consisted of 1 teacher in class B1 and 8 students as research subjects. After the data is collected, the data is presented to then draw a conclusion. The results of research on the character of hard work, independence and creativity are quite good. There are five steps in storytelling, namely determining the theme, setting goals, establishing the form of the story, supporting facilities and preparing the steps for assessing storytelling activities. It is hoped that teachers will add storytelling media that support and apply the five story methods to children according to the character they want to develop.